Perioperative nutrition according to the ERAS protocol - Małgorzata Nartowicz; Aleksandra Jaworska-Czerwińska; Małgorzata Chudzińska; Beata Pilarska; Ariel Liebert; Malwina Barańska; Kamila Tymosiak; Elżbieta Bernaciak; Walery Zukow (Kazimierz Wielki University, 2018)
Protocol ERAS - "Enhanced Recovery after Surgery" - is a modern multidisciplinary formula of perioperative care to improve treatment outcomes. Over the past few years, many attempts have been made to implement recommendations for the management of patients in the perioperative period. They were primarily aimed at improving the results of treatment of patients undergoing surgery, and thus shorteninglength of stay in hospital, and - as a consequence - reducing the risk of developing complications and even the number of deaths. One of the first author who noticed effectiveness of multimodal treatment for a faster recovery and a shorter stay in the hospital was Professor Henrik Kehlet from the University of Copenhagen. He emphasized that in order to understand the nature of complications occurring in patients undergoing surgery, the basis of the factors responsible for the response to the surgical trauma should be known. In the late 1990s, Kehlet postulated that steps should be taken to introduce a comprehensive program including, among others: effective anesthesia, early rehabilitation of the patient, reduction of surgical stress, or quick restoration of nutrition via the gastrointestinal tract. The comprehensive perioperative care protocol for improving the treatment results requires the need for cooperation of specialists and all medical staff related to perioperative care - not only a surgeon or anesthetist, but also a physiotherapist or dietitian.